Shadowing Technique to Improve the Students’ Pronunciation Ability in Narrative Text - Valesya Ellanda Oktavia Maldy; Sodiq``, Jafar; Ambarini, Ririn (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
This research is based on a study that looks at how shadowing technique can help eighth grade students at SMPN 37 Semarang improve their pronunciation. The purpose of this study was to find out how shadowing technique can improve pronunciation in one type of texts, a narrative text. This study aims to determine the following: (1) students' pronunciation achievement in narrative text before using the shadowing technique; (2) students' pronunciation achievement in narrative text after using the shadowing technique; and (3) to find out whether there is a significant improvement in students' English pronunciation in narrative text through the use of shadowing technique. The methodology of this study includes pre-experimental research. The pre-test and post-test are used in this study are how the researcher gathers data. In the data analysis, the researcher employs statistical computation using SPSS. This study used one eighth-grade class in SMPN 37 Semarang as its sample. There are 33 students in the class. The research’s data was gained from the students’ voice recordings. It is therefore evident from the pre- and post-test means. The pre-test outcome is 61.82. After receiving the treatment, the post-result is 90.85. Furthermore, the outcome of the hypothesis indicated that Ha is accepted. T-count exceeded T-table (17.693 > 1.694), which suggests that the shadowing technique noticeably improved pronunciation.